2016
DOI: 10.1159/000448102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the rs10767664 Variant of the Brain-Derived Neurotrophic Factor Gene on Weight Change and Cardiovascular Risk Factors in Morbidly Obese Patients after Biliopancreatic Diversion Surgery

Abstract: Background: The effect of the rs10767664 variant of the brain-derived neurotrophic factor gene on weight loss after bariatric surgery has not been evaluated. We decided to investigate the role of the rs10767664 variant on outcomes after biliopancreatic diversion surgery. Materials and Methods: A sample of 90 patients with morbid obesity without diabetes mellitus was operated. Biochemical and anthropometric evaluation were realized at basal visit and at each visit during 3 years (at 1, 2 and 3 years). Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…However, there is a lack of information about the influence of weight loss on this association in intervention studies. Only one study after weight loss intervention (bariatric surgery) has been performed, with the most prevalent SNP of the BDNF gene (rs10767664) [17]. In that study the rs10767664 variant of the BDNF gene did not influence weight loss or lipid profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a lack of information about the influence of weight loss on this association in intervention studies. Only one study after weight loss intervention (bariatric surgery) has been performed, with the most prevalent SNP of the BDNF gene (rs10767664) [17]. In that study the rs10767664 variant of the BDNF gene did not influence weight loss or lipid profile.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first dietary intervention randomized clinical trial where a different effect of a hypocaloric MUFAs-enriched diet was obtained. The influence of rs10767664 variant of the BDNF gene on the response of insulin and HOMA-IR after weight loss has not been described in the literature; only the effect of a huge weight loss (42 kg during 3 years of follow-up) after biliopancreatic diversion [17] has previously been described. The physiological mechanisms implied in this association of glucose metabolism and BDNF gene variants remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Follow‐up ranged from 6 months to 7 years. Weight loss was expressed as change in BMI in 11 studies, 25–34 percentage excess BMI loss (EBMIL) in one study, 35 percentage TWL in nine studies, 36–44 and excess weight loss (EWL) in 29 studies 45–73 . Patients underwent various types of bariatric procedures including RYGB, SG, and LAGB.…”
Section: Resultsmentioning
confidence: 99%
“…Follow‐up ranged from 6 months to 5 years. Changes in frequency of obesity‐related metabolic problems were reported in 18 studies, 32,40,47–60,68,72 and fasting glucose, HOMA IR, HbA1c, and/or lipids were reported in 21 studies 27,29,47–60,68,69,74–76 . One study used diabetes remission, defined as cessation of antidiabetic therapies, as outcome 34 .…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that not only the environment but also genetic variations account for successful weight-loss therapy [ 20 , 21 ]. Several genes as well as single nucleotide polymorphisms (SNPs) are associated with obesity phenotypes and weight loss after bariatric surgery [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Genetic Background and Bariatric Surgery Managementmentioning
confidence: 99%